2008
DOI: 10.1007/s11250-008-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine tuberculosis in Ethiopian slaughter cattle based on post-mortem examination

Abstract: A study aimed at describing the magnitude and distribution of gross lesions compatible with bovine tuberculosis (BTB) in Ethiiopian slaughter cattle in five abattoirs (four municipal and one export) located in various cattle husbandry systems in Ethiopia was carried out from July 2006 to January 2007 using detailed meat inspection procedure. Five representative abattoirs (four municipal and one export) located in distinct livestock management systems were selected. A total of 3322 cattle; 2876 (86.6%) male, 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
50
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 26 publications
13
50
2
1
Order By: Relevance
“…In addition, the prevalence of BTB in cattle from Tamaulipas that were exported to and slaughtered in The considerably higher prevalence for the year 1995 was expected because at that time, there were no activities focused in the control of BTB. After the reduction of the prevalence in 1996, there was a slightly rising of this pattern in subsequent years (1997 and 1998), which is consistent with the previously reported in other studies (PAHO, 1992;Tadayon et al, 2008;Demelash et al, 2009). The aforementioned increment is consequence of detecting as positive to skin test animals infected with other Mycobacterium spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the prevalence of BTB in cattle from Tamaulipas that were exported to and slaughtered in The considerably higher prevalence for the year 1995 was expected because at that time, there were no activities focused in the control of BTB. After the reduction of the prevalence in 1996, there was a slightly rising of this pattern in subsequent years (1997 and 1998), which is consistent with the previously reported in other studies (PAHO, 1992;Tadayon et al, 2008;Demelash et al, 2009). The aforementioned increment is consequence of detecting as positive to skin test animals infected with other Mycobacterium spp.…”
Section: Discussionsupporting
confidence: 89%
“…For livestock production, BTB is cause of high economic losses due to reduced production, culling of infected animals and condemnation of carcasses (Diguimbaye-Djaibé et al, 2006;Proaño-Perez et al, 2006;Elias et al, 2008). Furthermore, the disease constitutes a barrier for the international trade of livestock when is prevalent in a region (Cousins, 2001;Demelash et al, 2009). In Mexico, the economic losses due to the presence of BTB could be calculated in the order of US$ 450 million, as consequence of a limited exportation of livestock to the United States of America (DOF, 1996).…”
mentioning
confidence: 99%
“…Demelash et al (2009) showed that the Se of histopathology diagnosis can be affected by the technique used and the number of slides examined. In our study, two slides per specimen were examined, i.e., after HE and after ZN staining.…”
Section: Discussionmentioning
confidence: 99%
“…In countries like Ethiopia, implementation of detailed necropsy examination of carcasses at slaughter houses continues to be an important step in surveillance [17]. The present study was conducted on cattle slaughtered at Gondar ELFORA abattoir; a number of people are involved in feed lot production systems supplying cattle to surrounding slaughter house.…”
Section: Introductionmentioning
confidence: 99%